2014
DOI: 10.1175/waf-d-13-00047.1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Convective Morphology in Near-Cloud-Permitting WRF Model Simulations

Abstract: The Weather Research and Forecasting (WRF) model’s ability to forecast convective morphological evolution is examined for 37 convective systems. The simulations used Thompson microphysics with 3-km horizontal grid spacing. Ten convective mode classifications were used. An objective score was developed to determine the accuracy of the simulated morphologies considering a normalized duration of each mode simulated and its agreement with observations. Rapid Update Cycle analyses were used to compare larger-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…Several studies can be found, where predictability of MCSs within a convectionpermitting resolution is provided. In spite of limitations associated with initial conditions and physical parameterizations, in many studies it was possible to perform a successful MCS forecast along with mesoscale features such as MCV, RIJ or bow echo (e.g., Melhauser and Zhang 2012;Weisman et al 2013;French and Parker 2014;Snively and Gallus 2014;Xu et al 2015a,b, among others). Weisman et al (2008) used the Weather Research and Forecasting (WRF) Model (Skamarock et al 2008) and a horizontal resolution of 4 km to perform 0-36-h real-time explicit convective forecasts and concluded that a significant improvement was observed FIG.…”
Section: Predictabilitymentioning
confidence: 99%
“…Several studies can be found, where predictability of MCSs within a convectionpermitting resolution is provided. In spite of limitations associated with initial conditions and physical parameterizations, in many studies it was possible to perform a successful MCS forecast along with mesoscale features such as MCV, RIJ or bow echo (e.g., Melhauser and Zhang 2012;Weisman et al 2013;French and Parker 2014;Snively and Gallus 2014;Xu et al 2015a,b, among others). Weisman et al (2008) used the Weather Research and Forecasting (WRF) Model (Skamarock et al 2008) and a horizontal resolution of 4 km to perform 0-36-h real-time explicit convective forecasts and concluded that a significant improvement was observed FIG.…”
Section: Predictabilitymentioning
confidence: 99%
“…Este problema pode ser devido à má representação da umidade específica e de água precipitável pelo modelo, que prejudica o desempenho da simulação da temperatura do ar (Bromwich et al, 2013) e pelo déficit no fluxo de ondas longas (Guo et al, 2003) sobre a Antártica. Outros estudos mostraram que o modelo WRF não simulou adequadamente a precipitação de chuva de nuvens estratiformes, por exemplo, Snively & Gallus Jr. (2014). Essa deficiência na cobertura de nuvens simulada pelo WRF pode impactar na correta estimativa das temperaturas.…”
Section: Simulação Numérica Regional Para a Temperatura Do Ar No Continente Antártico Cominunclassified
“…Before reaching the archives, Base Reflectivity product data are composited with the GEMPAK program nex2img, after which false echoes are removed after comparison with the Net Echo Top product. Total absolute SAL (taSAL) is computed as follows: (1) and varies between 0 (perfect forecast) and 6. The three components are combined this way in the absence of strong evidence to suggest otherwise, though unequal weightings are used in similar schemes (e.g., Method for Object-Based Diagnostic Evaluation; [33]).…”
Section: Verification and Spreadmentioning
confidence: 99%
“…Within the group of mesoscale convective systems (MCSs), systems that display bowing structures along the convective line are among the most poorly forecast [1]. Lawson and Gallus [2] showed that smaller (progressive) bow echoes were likely poorly forecast due to inherent low predictability more so than deficiencies in microphysical parameterizations, and that improvements in synopticand mesoscale initial and lateral-boundary conditions (ICs and LBCs, respectively) would yield only minor skill increases at best.…”
Section: Introductionmentioning
confidence: 99%